A Critical Review of Sports Events Practice - Getu Yemiru, Zemikael (ETHIOPIAN JOURNAL OF SPORT SCIENCE, 2021)
This paper will illustrate the meaning and importance of sports event management, the typology of sports events, the specialization of sports events, and the model of sport event management. This study used the literature review method to acquire its final results. The relevant sport event management literature review was done according to the purpose of the study. It used the purposive random sample method for selecting relevant literature. This study shows the current typology of the event in the sports industry; the second part of the study critically analyzes the different ways of specializing in sport event management. It also critically evaluates the sports event management model and the reason for some sports failures; therefore, Events also have the power to show sustainability in action, and every sustainably produced event can inspire and motivate others to action.